Comparative Anatomical Study of Beak in Domestic Fowls - Hamid, Asadullah (Journal of Natural Sciences – Kabul University, 2023)
The beak is a critical component of the fowl skeleton. Unlike mammals, fowls lack teeth; instead, their upper and lower jaws are elongated, forming a species-specific beak. The beak functions as both hand and mouth in fowls and is used for food intake, feather trimming, collecting food, building nests, feeding chicks, and self-defense. This research examines the beak structure in various domestic fowls. Beak specimens were collected from the anatomy laboratory and measured using a simple ruler. The findings reveal that the structure and size of beaks vary depending on food types, feeding habits, and environmental conditions.